El atletismo y su influencia en el desarrollo motor en estudiantes de primer grado de educación primaria de la Institución Educativa Mariscal Oscar R. Benavides, Iquitos 2022 - Ahuanari Valles, Marcelo (2025)
The general objective of this study was to determine the effects of athletics on motor development. The nature of the research is an observational and cross-sectional project. The population consisted of 101 students, which served as a sample. The data collection tool was an observation sheet for each research variable. The same one who worked in expertise and obtained a score of 97.3% and a reliability of 79.5% in the sport variable and 88.2% in the motor development variable, important for its application. The normality test was carried out using the Kolmogorov-Smirnov (K-S) test statistic, where it was shown that the data do not follow a normal distribution. In the hypothesis contrast, the Kendall Tau_b test statistic was used. After carrying out the hypothesis test, it was determined that there is no significant influence of athletics on motor development in first grade students of primary education at the Mariscal Oscar R. Benavides institution, Iquitos 2022.